ANALYSIS OF NUTRIENTS, TOTAL PHENOLS AND ANTIOXIDANT ACTIVITY OF FICUS SANSIBARICA WARB. FRUITS FROM EASTERN BOTSWANA - Daniel, Motlhanka; Topo, Ebineng (Journal of Drug Delivery and Therapeutics, 2012)
Ripe fruits of Ficussansabarica were assessed for in vitro antioxidant activity using the Free radical scavenging assay (FRSA). The scavenging activity of the fruits was evaluated spectrophotometrically as maximum fading power of1,1-Diphenyl-2-picrylhydrazyl (DPPH) at 525nm. The total phenolic content of water and methanol extracts was determined using the Folin-Ciocalteau method. The mineral composition of the fruits was analyzed using the optical emission spectrophotometer. At all tested concentrations the scavenging power of methanolic extract was higher than that of water extract. Between 100 and 200Âµg/ml, both extracts exhibited scavenging power of â‰¥85% comparable to the standard compound quercetin. The total phenolic contents of water and methanolic extracts were 3145 and 3584 mg/L GAE, respectively. The fruits contained 7.83mg/LCa,9.47mg/LMg,2.66mg/L Na, 58.1mg/L K, and 0.02mg/L P. Crude protein content as determined by the Kjeldahl method was 0.18%. These results show that these fruits are a rich source of the essential elements that have a positive effect on human health. The results support the use of these fruits as supplements for nutrient deficiencies and for combating diseases associated with oxidative damage. Keywords: mineral content; Ficussansabarica; total phenols; free radical scavenging; wild fruits.